Adding to the Arsenal of Zirconium‐Based Metal–Organic Frameworks: the Topology as a Platform for Solvent‐Assisted Metal Incorporation. Issue 27 (8th July 2016) - Liu, Tian‐Fu; Vermeulen, Nicolaas A.; Howarth, Ashlee J.; Li, Peng; Sarjeant, Amy A.; Hupp, Joseph T.; Farha, Omar K.
Abstract : Gaining control over the assembly of mesoporous Zr‐based metal–organic frameworks (MOFs) with modifiable metal nodes remains a challenge. The the topology is intriguing, particularly if considering postsynthetic modification, as it presents large sodalite‐like cages surrounded by 12 interconnected 1D channels that allow for efficient diffusion of guest molecules throughout the structure. Herein, we demonstrate the first Zr MOF with the topology, NU‐1200, which was synthesized by controlling the geometry of the organic building unit. In addition, by using NU‐1200 as a platform, we perform solvent‐assisted metal incorporation to form single‐site metalated nodes, a process that is characterized by single‐crystal X‐ray diffraction. Abstract : NU‐1200 is a Zr‐based metal–organic framework (MOF) with the topology. Consisting of unsaturated Zr6 oxide nodes and triangular linkers with large interconnected channels, this MOF is an ideal candidate for postsynthesis metalation.